Multi-Disciplinary Analysis of Working Fluids on Thermal Performance of the High-Power Diesel Engine System - Geesoo Lee (Machines, 2022)
Multi-disciplinary analysis was performed to analyze and investigate the thermal performance during transient operation of a 2 L diesel engine system with two different cooling systems. The multi-disciplinary model consisted of the engine thermal management system (ETMS) comprising a zero-dimensional engine model that can simulate the engine performance, and a one-dimensional flow model for cooling and lubrication systems with a controller. By deploying this approach, we were able to model different physical domains, including mechanical for the engine and the dynamometer and thermodynamic for the heat exchangers. Therefore, the thermal performance of the ETMS could be numerically predicted and analyzed. To develop the ETMS model, the physical properties, the heat transfer model, and the pressure drop were modeled. The base fluid, a 50/50 mixture of water and ethylene glycol (EG), and an Al2O3 nanofluid with a 1.5% volume ratio were modeled based on the thermodynamic properties such as density, dynamic viscosity, thermal conductivity, and specific heat. Nanofluid, with its higher thermal conductivity and higher heat transfer coefficient, absorbed more heat from the combustion chamber through the water-jacket in the engine block. Therefore, the oil temperature for the nanofluid was effectively 2.5 °C less than for the base fluid following the step-load condition. Simulation results showed the better effect of nanofluid on thermal performance. The total flow rate of nanofluid decreased by 2.2 L/min, although the flow rate through the radiator with nanofluid increased by 0.81 L/min to obtain greater heat dissipation. Eventually, the piston and the liner temperatures with the nanofluid were drastically reduced by 7.55 and 8 °C, respectively, compared to those of the base fluid. Finally, when nanofluids was applied in automotive cooling systems, the temperature of the piston decreased by 7.3 °C due to the reduced overall thermal resistance from combustion chambers to outside air. The effect of working fluid on the diesel engine system could be predicted through the multi-disciplinary model.